Satisfactions of Customers by Using Online Food Application Services During Covid-19 Pandemic - Rosa, Honeylyn R. Dela; Separa, Lenis Aislinn C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Food businesses benefit from an online food ordering and delivery framework. The purpose of this study is to identify the factors that influence overall consumer satisfaction with online food delivery providers. The demographic information of the respondents was discussed in this study. Furthermore, this study also revealed a significant difference between respondents' perceptions of e-services and the variables listed in the study's objectives. The researchers used a quantitative approach to identify the factors that influence consumers' overall satisfaction with online food delivery services. To collect information from the respondents, the researchers used a convenience and snowball sampling technique. Descriptive statistics were used to depict the respondent profile. The Mann-Whitney U and Wilcoxon tests were used to determine the difference in e-satisfaction between female and male respondents, while the Kruskal-Wallis test was used to determine the difference in e-satisfaction of respondents when grouped by age. The Spearman rho was used to see if there was a link between personal aspect, E-Service Quality, and Perceived Food Quality and e-satisfaction. The study found a significant relationship between personal aspect, E-Service Quality, and Perceived Food Quality and e-satisfaction. In terms of gender, most of the respondents are male, with 51.3%, and for the age of respondents, 29 to 40 years old. In terms of employment status, employed with a total of 162 and 61.60% has participated in the study. income salary, 50,000 and above are the highest, with a frequency of 64 and a percentage of 27.71%.